2021
DOI: 10.1186/s12879-021-06767-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis and other infections in pregnant women in Senegal

Abstract: Background Bacterial vaginosis (BV) is associated with a higher risk of preterm delivery and spontaneous abortion. Yet little data on BV prevalence exist for sub-Saharan countries. The aim of this study was to estimate the prevalence of bacterial vaginosis and associated risk factors among pregnant women in Senegal. Methods From October 2013 to December 2018, pregnant women in their third trimester were recruited in two primary health centers (one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
2
4
0
2
Order By: Relevance
“…This obtained prevalence of BV is within the expected range for African women, that's 25-50% [17]. This prevalence rate was higher than those reported by previous studies in Senegal, with rates ranging from 21% [18] to 18.6% [19].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This obtained prevalence of BV is within the expected range for African women, that's 25-50% [17]. This prevalence rate was higher than those reported by previous studies in Senegal, with rates ranging from 21% [18] to 18.6% [19].…”
Section: Discussionsupporting
confidence: 81%
“…In our study, women in the [16][17][18][19][20][21][22][23][24] age group had a higher prevalence of BV and this had been reported in the work of Ibrahim SM et al, in 2014, in Maiduguri in North East Nigeria [27].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A study on pregnant low-income African-American women reported a prevalence of 25% [13]. Similarly, another study in the sub-Saharan African countries suggested variations in the BV prevalence from 25 to 50% and from 9 to 23% [23].…”
Section: Discussionmentioning
confidence: 94%
“…The search strategies yielded a total of 2238 records; among them, 12 studies [2,5,6,15,[17][18][19][20][21][22][23][24] met the inclusion criteria and were included in the qualitative synthesis. The article selection process is shown in the PRISMA ow diagram (see Fig.…”
Section: Resultsmentioning
confidence: 99%